A simple and evolutional approach proven to recanalise the nasolacrimal duct obstruction. Issue 11 (4th May 2009) - Chen, D; Ge, J; Wang, L; Gao, Q; Ma, P; Li, N; Li, D-Q; Wang, Z
Abstract : Aim: To evaluate a new approach of recanalisation of nasolacrimal duct obstruction (RC-NLDO) in the treatment of the nasolacrimal duct obstruction (NLDO) and chronic dacryocystitis. Methods: 583 patients with 641 eyes suffering from NLDO and chronic dacryocystitis were enrolled in this study. The RC-NLDO was performed in 506 eyes, with 135 eyes undergoing external dacryocystorhinostomy (EX-DCR) as controls. Patient follow-up for 54 months was evaluated by symptoms, dye disappearance test, lacrimal irrigation and digital subtraction dacryocystogram. The RC-NLDO was also performed in 12 rhesus monkeys for histopathological examination. Results: The clinical success rates were 93.1% in 506 cases of RC-NLDO and 91.11% in 135 cases of EX-DCR. The success rates for second surgery were achieved in 85.19% on RC-NLDO and 40.0% on EX-DCR. No major intra- or postoperative complications were observed in the RC-NLDO group. The mean operative duration was 12.5 min for RC-NLDO and 40.3 min for EX-DCR (p<0.001). A pathological study in rhesus monkeys demonstrated that the RC-NLDO wounded epithelium in nasolacrimal duct healed completely within 1 month without granulation tissue formation. Conclusion: The findings demonstrate that the RC-NLDO is a simple and effective approach proven to recanalise the obstructed nasolacrimal duct with a comparable success rate to EX-DCR.